Influence of Injection Molding Parameters and Distance from Gate on the Mechanical Properties of Injection-Molded Polypropylene - Fucikova, Klara; Ovsik, Martin; Cesnek, Adam; Pis, Adam; Vanek, Jiri; Stanek, Michal (Polymers, 2025)
This publication deals with the study of the mechanical properties of injection-molded polypropylene parts depending on the process parameters and the distance from the gate location in which the mechanical properties were investigated. Due to the fact that the mechanical properties of injection-molded parts are not the same at all locations, this research was designed to investigate the inhomogeneity of the properties of injection-molded parts along the length of the product. The inhomogeneity is affected by various influences, including distance from the sprue mouth, melt and mold temperature, injection pressure, crystal structure, and others. It was demonstrated that mechanical properties are not uniform over the entire injected product. Contrary to popular belief, mechanical properties can vary along the flow length due to uneven cooling and process parameters. Injection pressure and mold temperature significantly affect the mechanical properties of the injection-molded parts. The limiting injection pressure is 40 MPa and the mold temperature is 40 °C. The difference in individual spots in an injected article was up to 37%. Changes in mechanical properties are closely related to changes in morphology (crystallinity measured by DSC) caused by different injection molding process parameters. As is evident from the aforementioned results, the possible benefits of this work for injection molding of polymer products are apparent. Suitably chosen gate location, surface of the cavity, and process parameters can ensure targeted improvement of mechanical properties in stressed parts of a product.
Keywords: injection molding; mold temperature; polypropylene; indentation hardness; injection pressure; mechanical properties